1983
DOI: 10.1128/mcb.3.6.967
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of an alpha-satellite array by a short member of the KpnI family of interspersed, highly repeated monkey DNA sequences.

Abstract: We describe here the interruption of a cloned African green monkey a-satellite array by an 829-base-pair-long nonsatellite DNA segment. Hybridization experiments indicate that the sequences within the interruption are homologous to segments frequently found in the 6-kilobase-pair-long members of the KpnI family of long, interspersed repeats. These data confirm and extend earlier results suggesting that sequences common to the KpnI family can occur independently of one another and in segments of variable length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 23 publications
2
39
0
Order By: Relevance
“…Southern blots indicated that the inserted element in the pa7 clone is homologous to three of the "consensus" Kpn I subclones and, therefore, is a member of the Kpn I family. (12). Second, and perhaps more interesting, the sequences that are present appear to be permuted or scrambled relative to the "normal" consensus arrangement exemplified by Kpn /.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Southern blots indicated that the inserted element in the pa7 clone is homologous to three of the "consensus" Kpn I subclones and, therefore, is a member of the Kpn I family. (12). Second, and perhaps more interesting, the sequences that are present appear to be permuted or scrambled relative to the "normal" consensus arrangement exemplified by Kpn /.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore any sequences interrupting satellite DNA might well represent mobile elements that were inserted in recent evolutionary time. I and others have previously reported the isolation of satellite DNA segments carrying such nonsatellite sequences (10,(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, DNA sequences from portions of the monkey LI (Kpn I) family have been published (22,39). The available sequence includes a region that is homologous to the sequence from LJMd-4 and other published LJMd sequences (see ref The values for "possible sites" were determined by examining all three possible base substitutions at each position in the sequence and determining whether the altered codon represents a silent (S) or replacement (R) substitution.…”
mentioning
confidence: 99%